Demand for International Reserves in Less Developed Countries: A Distributed Lag Specification - Iyoha, Milton A. (The Review of Economics and Statistics, 1976)
IN this paper an attempt is made to ascertain the determinants of the demand for international reserves by the monetary authorities of the less developed countries (LDCs).' An important aim of the paper is to improve on the specifications of the demand-for-reserve functions that exist in the literature.2 The model presented improves on existing ones in many respects, including (i) the concepts of actual and optimum reserves are differentiated and the relationship between them rigorously specified; (ii) the determinants of the optimum level of international reserves are obtained by maximizing an intertemporal, stochastic macroeconomic model;3 (iii) an expected export earnings variable is estimated and used as an explanatory variable; and (iv) distributed lag adjustment is introduced. In the next section a modified partial adjustment model is specified. The equation to be estimated has a second-order lag scheme. In section III the estimation methods and data sources are discussed. Estimation of the demand function is done in two steps: first, export earnings functions are estimated for the twentynine LDCs in the sample during 1950-1969. From these, we obtain two variables expected export earnings and an export instability index to use with others in the cross-country equation. Next, a country cross-section regression analysis is carried out for 1970. Steadystate elasticities are calculated and the results are discussed.